2021
DOI: 10.3389/fphar.2021.661304
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nicotine Exposure Alters Hippocampal Microglia Polarization and Promotes Anti-inflammatory Signaling in Juvenile Offspring in Mice

Abstract: Accumulating evidence reveal that maternal smoking or perinatal nicotine replacement therapy impairs hippocampal neurogenesis, neural development, and cognitive behaviors in the offspring. Microglia is a source of non-neural regulation of neuronal development and postnatal neurogenesis. In this study, we explored the impact of nicotine on the microglia during the development of hippocampus. Developmental nicotine exposure in a mouse model was conducted by supplementing nicotine in the drinking water to mother … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Nicotine induced immunosuppression is associated with preserved insulin content and reduced incidence of diabetes in T1D-prone mice models 42 . Experimental studies indicate that the immunosuppressive and anti-inflammatory effects of prenatal smoking exposure remain also postnatally 43 44 . The hypothesis of immunosuppression is partly supported by the fact that autoantibodies of T1D mostly appear within the first two years after birth, close to the time of fetal exposure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine induced immunosuppression is associated with preserved insulin content and reduced incidence of diabetes in T1D-prone mice models 42 . Experimental studies indicate that the immunosuppressive and anti-inflammatory effects of prenatal smoking exposure remain also postnatally 43 44 . The hypothesis of immunosuppression is partly supported by the fact that autoantibodies of T1D mostly appear within the first two years after birth, close to the time of fetal exposure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Developmental nicotine exposure has resulted in adverse outcomes in vitro and in vivo [ 14 , 15 , 16 , 17 ]. Even though test protocols and drug concentrations vary from those in our study, the previous studies support our major observations: (1) reduced motor learning, (2) compulsive behavior, (3) decreased cognition, and (4) alternation in social interaction patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Picciotto (2019) reported that nicotine exposure (delivered thorough drinking water; 200 μg/mL) during development impairs learning behaviors and motor tasks via the modification of cortical synaptic plasticity. Zhou (2021) revealed that maternal nicotine exposure (via drinking water; 200 μg/mL) resulted in increased moving distance in an open field test for offspring mice [ 17 ]. Moreover, Alkam (2013) reported that maternal nicotine exposure (via drinking water; 200 μg/mL, ad libitum ) weakened the emotional behaviors of offspring mice, including those displayed in the marble-burying test.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine-induced immunosuppression is associated with preserved insulin content and reduced incidence of diabetes in type 1 diabetes-prone mice models [49]. Experimental studies indicate that the immunosuppressive and anti-inflammatory effects of prenatal smoking exposure remain also postnatally [50,51]. The hypothesis of immunosuppression is partly supported by the fact that autoantibodies of type 1 diabetes mostly appear within the first 2 years after birth, close to the time of fetal exposure [2].…”
Section: Potential Mechanismsmentioning
confidence: 99%